Recent advances in information and communication technology 2018 proceedings of the 14th International Conference on Computing and Information Technology (IC2IT 2018) /: proceedings of the 14th International Conference on Computing and Information Technology (IC2IT 2018). (c2019) - Unknown
No abstract available